The Natural Situation and Its Effective Role in Designing Arabic Listening Skills Teaching Materials for Non-Native Speakers/ المواقف الطبيعية ودورها الفعال في استمدادها مادة مهارة الاستماع للناطقين بغيرها - Rosyad, Muh Sabilar; Adam, Faishol Mahmoud; Bahruddin, Uril (Ijaz Arabi Journal of Arabic Learning, 2023)
There is a phenomenon of decreasing students' tendency and interest in learning listening skills. It is assumed that the underlying cause is the use of teaching materials and learning serial books, which contain several patterns and cultural dimensions that do not have direct contact with the conditions of students and their surroundings, even their academic and social experiences. This study aims to 1) Design teaching materials for the listening skills derived from the students' natural situations and 2) discover their validity and suitability for teaching listening skills in the Department of Arabic Language Education. This study uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) research and development model developed by Reiser and Mollenda. Data collection methods were obtained through observation, interviews, and questionnaires, while the analysis technique used descriptive quantitative analysis. The results of this study are: 1) Natural situation-based teaching materials are designed with a student contextual approach consisting of teacher books and student books, where each book contains thirteen learning themes, each theme includes two learning materials, and each learning material contains audiovisual texts and listening exercises. 2) The Listening Skills teaching materials designed using the natural situation approach were declared valid based on the assessment of two experts with a total score of 94.75%, and the predicate was very good. The teaching material is considered feasible and suitable for improving students' listening skills and arousing their interest based on the value of the questionnaire, which reaches a percentage above 90%. The theoretical conclusion of this study is that using listening skills and teaching materials based on a natural situation is more appropriate and able to attract students' attention and inclinations in the learning process.